A rare case of a prostatic abscess, bacteremia and chronic granulomatous disease associated with Klebsiella pneumoniae. Issue 5 (May 2019) - Wakabayashi, Yoshitaka; Jubishi, Daisuke; Okamoto, Koh; Ikeda, Mahoko; Tatsuno, Keita; Mizoguchi, Miyuki; Sato, Tomoaki; Okugawa, Shu; Moriya, Kyoji
Abstract: Chronic granulomatous disease (CGD) is a primary immunodeficiency disease characterized by severe recurrent infections such as pneumonia, liver and skin infections. However, prostatic abscesses are rare as only two cases have been reported thus far. We present the case of a 41-year-old patient with CGD who was admitted to the hospital with fever and subsequently, Klebsiella pneumoniae was identified on blood culture. Abdominal computed tomography revealed a prostatic abscess. He improved with intravenous antibiotics and drainage of the abscess. After he was taken off the intravenous antibiotics and started on an oral agent, he was discharged from the hospital. We confirmed a reduction in the prostatic abscess size and continued the antibiotic therapy for 52 days. A prostatic abscess is an uncommon disease being diagnosed at a median age of 49 years. Sometimes it is discovered in patients with fever of unknown origin and might be considered as an infection site of CGD patients.